Drug–Drug Interactions Based on Pharmacogenetic Profile between Highly Active Antiretroviral Therapy and Antiblastic Chemotherapy in Cancer Patients with HIV Infection - Berretta, Massimiliano; Caraglia, Michele; Martellotta, Ferdinando; Zappavigna, Silvia; Lombardi, Angela; Fierro, Carla; Atripaldi, Luigi; Muto, Tommaso; Valente, Daniela; De Paoli, Paolo; Tirelli, Umberto; Di Francia, Raffaele (Frontiers in Pharmacology, 2016)
The introduction of Highly Active Antiretroviral Therapy (HAART) into clinical practice has 27 dramatically changed the natural approach of HIV-related cancers. Several studies have shown that 28 intensive antiblastic chemotherapy (AC) is feasible in HIV-infected patients with cancer, and that the 29 outcome is similar to that of HIV-negative patients receiving the same AC regimens. However, the 30 concomitant use of HAART and AC can result in drug accumulation or possible toxicity with 31 consequent decreased efficacy of one or both classes of drugs. In fact, many AC agents are 32 preferentially metabolized by CYP450 and drug-drug interactions (DDIs) with HAART are common. 33 Therefore, it is important that HIV patients with cancer in HAART receiving AC treatment at the 34 same time receive an individualized cancer management plan based on their liver and renal 35 functions, their level of bone marrow suppression, their mitochondrial dysfunction and their 36 genotype profile. The rationale of this review is to summarize the existing data on the impact of 37 HAART on the clinical management of cancer patients with HIV/AIDS and DDIs between 38 antiretrovirals and AC. In addition, in order to maximize the efficacy of antiblastic therapy and 39 minimize the risk of drug-drug interaction, a useful list of pharmacogenomic markers is provided.